HIV-1 genetic diversity and reverse transcriptase resistance mutations in Benin before dolutegravir era, West Africa - Edmond Tchiakpe; René Kpemahouton Keke; Patricia Recordon-Pinson; Abou Abdallah Malick Diouara; Marie-Line Andreola; Moussa Bachabi; Aldric Afangnihoun; Eric Gbaguidi; Sophia Osawe; Almoustapha Issiaka Maiga; Halimatou Diop-Ndiaye; Coumba Touré-Kane; et al. (PLoS ONE, 2026)
Benin adopted the World Health Organization’s (WHO) “Test and Treat” recommendation in 2016 and, since 2019, has updated this protocol by including dolutegravir (DTG) as the preferred first-line treatment. Study aimed to assess the prevalence of virological failure (VL > 3log copies/mL) and review genetic diversity and antiretroviral resistance mutations in patients on antiretroviral treatment for at least 12 months before dolutegravir Era in Benin. Cross-sectional study included patient plasmas from antiretroviral treatment sites nationwide. Viral load was performed in National Reference Laboratory of Health Program Fighting Against AIDS using the Cobas® 5800 HIV-1 assay. For plasmas those VL above 1000 copies/mL, nested PCR were done along the entire protease and part of reverse transcriptase. The DNA obtained by the Sanger method was used to determine the subtypes of HIV-1 after editing with DNASTAR SeqMan Pro™ and alignment with ClustalW2 version 2.1. Phylogenetic trees were constructed by the Neighbor-Joining method and recombinants were investigated by bootscanning with Seaview software version 2.1. DNA was subjected to the Stanford University Antiretroviral Resistance Mutation Interpretation Algorithm ( https://hivdb.stanford.edu/ ) to identify the positions of drug-associated resistance mutations. (178/253; 70.35%) of the samples were correctly amplified and sequenced. CRF02_AG (n = 104) was the predominant strain observed followed by CRF06_cpx (n = 21), G (n = 5), CRF43_02G (n = 2), CRF37_cpx (n = 2), A1 (n = 1) and unique recombinant forms (URFs) (n = 34) among the 169 samples sequenced on entire protease combined with part of the reverse transcriptase. (164/178; 92.1%), (141/178; 79.2%), (160/178; 89.9%) and (7/169; 4.1%) patients carried at least one drug resistance associated to NRTIs, NNRTIs and PIs respectively. M184I/V, TAMSI: (M41L, L210W, T215Y) and TAMSII: (D67N, K70R, K219Q/E, T215I/V) represented (71.3%), (21.9%), (35.4%) respectively. K103N/S was the most preponderant mutations encountered with a proportion of 64.6% followed by V179E (21.3%), P225H (20.2%), V108I (19.1%), Y181C (16.3%), A98G (15.2%), V106I/M/A (10.1%). I84V (1.8%) mutation was the major associated PIs encountered followed by L90M, V82A, M46I each encountered twice (1.2%) and I47A, V32I, I54V, G48A, each encountered once (0.6%). Study shows a high genetic diversity with the presence of new strains and underlines the need to regularly review data on genetic diversity and resistance among patients receiving antiretroviral therapy in the country.